The impact of women power on firm value - Tiago Cruz Gonçalves; Cristina Gaio; Micaela Rodrigues (Administrative Sciences, 2022)
Companies have been encouraged by policy to place women on board and top management positions. Proposals from regulators and governance reforms explicitly stress the importance of gender diversity in the boardroom. This paper analyzes the impact of the presence of women in executive and non-executive positions, as Chairs, CEOs or CFOs, on firm value in the context of European public companies. The results suggest that the presence of women impacts firm value positively. The results also suggest that, in countries governed by women, firm values are higher. A further analysis provides evidence that, when women CEOs and Chairs are simultaneously shareholders, firm value is negatively impacted. In contrast, when a Chair changes from a man to a woman, firm value is positively impacted. This study contributes to the ongoing debate on whether appointing women to board positions and management positions has positive valuation effects, and it is of the interest to policymakers and investors, among others.
Keywords: 350; board; CEO and CFO; chairperson; firm value; gender diversity